A Complete Edition of an Oral Tradition: Text Selection Practices in the History of Publishing Latvian Folk Songs. Issue 1 (2nd January 2017) - Bula, Dace
Abstract: This article addresses the history of publishing folklore texts—particularly the attempts at creating all-inclusive publications that would represent an oral tradition in its entirety. Despite the quest for comprehensiveness, these attempts have always entailed the need to be selective in order to draw textual boundaries within the unbounded, diverse folk singing repertory. The focus of this study is on the text selection principles applied by two editors of Latvian folk songs: Krišjānis Barons (1835–1923) and Pēteris Šmits (1869–1938).